Optimization of Palm Frond Pulping Using a Soda-Anthraquinone Process in a Circulating Digester: A Sustainable Approach - Suhendri, Suhendri; Evelyn, Evelyn; Setiadi, Tjandra; Risdianto, Hendro (Eksergi, 2025)
Oil palm fronds, typically discarded after pruning, have potential as a raw material due to their lignocellulosic content. This study optimizes the soda-anthraquinone pulping process using a circulating digester. It investigates the effects of cooking temperatures (140, 150, and 160°C), cooking times (120, 180, and 240 minutes), and NaOH concentrations (10%, 15%, and 20%) with 0.1% anthraquinone, employing Response Surface Methodology (RSM) based on Central Composite Design (CCD). Analysis with Design Expert 13 software revealed significant impacts on yield (19.01-31.00%), kappa number (9.24-15.69), and viscosity (2.91-34.45 cP). Optimal conditions were 140°C, 120 minutes, and 10% NaOH, yielding 30.57% pulp, kappa number of 13.87, and viscosity of 24.03 cP. This research underscores the environmental benefits of utilizing palm fronds, contributing to waste reduction and circular economy practices, and demonstrates the potential for industrial scalability, offering a sustainable alternative to traditional pulping methods.